Impacts of climate change on cropping pattern in coastal region of Bangladesh : a case study of Sharankhola Upazila , Bagerhat - Ali, Md. Mohosin (BRAC University, 2013)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2012.